FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT KECEMASAN PEREMPUAN DALAM MENGHADAPI MENOPAUSE DI WILAYAH KERJA PUSKESMAS KUTA BARO ACEH BESAR - Nurul Amna; Khaira Rizki; Ellyza Fazlylawati; Munawarah (Cahaya Ilmu Bangsa Institute, 2024)
Women who had menopause experience several physical and psychological changes, changes that occur such as painful intercourse, vaginal dryness and painful urination. Apart from that, changes occur in the skin such as dry and thinning skin and calcium levels decreasing by 35-45%, psychological disorders such as anxiety, irritability, depression and insomnia by 50%, libido decreases by 30%. The aim of the research is to determine the factors that influence women's anxiety levels in facing menopause in the Kuta Baro Aceh Besar Health Center Work Area.This research method uses a cross sectional approach with a population of 1,235 people and a sample size of 93 women aged 45-59 year, the sampling technique is Stratified Random Sampling. For the anxiety variable, the DASS-21 instrument was used and the knowledge variable used a Likert scale questionnaire. The results of univariate analysis showed that of the 93 respondents, the majority experienced anxiety in the mild category, 43.0%, had low knowledge about menopause, 63.4% and 36.6% had high knowledge, 40.9% had secondary education and were in early adulthood. as much as 54.8%. The results of bivariate analysis using the chi-square test showed that there was a relationship between knowledge (p=0.002), education (p=0.004) and age (p=0.003) on anxiety in facing menopause. It is hoped that nurses at Community Health Centers will provide education for women who will and are facing menopause, so that they can increase women's knowledge and readiness to face menopause